Traditional and Actual Aspects in Modern Academic Art History Education - Gracheva, Svetlana M. (Actual Problems of Theory and History of Art, 2022)
The methods of teaching art history in The Academy of Fine Arts in the 20th century always were based mainly on a concept of a connoisseur art science. The students of the Academy of arts must deeply understand the nature of creativity, so in addition to studying theoretical and historical disciplines. The art historian students at the Academy of arts spend many hours drawing and painting. They have a unique opportunity to study the technique and technology of art materials in academic laboratories and production workshops. Traditionally, an art historian who graduated from the Academy of arts works in a museum, teaches, works as an art critic, art expert, or deals with attribution of works of art. Now the boundaries of the profession have expanded, thanks to the emergence of curatorial institutions, art dealers, gallery business, the expansion of virtual space, and contemporary art strategies. Modern art history education is influenced by postmodern aesthetics and cultural studies, philosophy, the innovative technologies, the demands of an information and communication constantly changing market society, and so on. The problem of understanding the authenticity of an art work in the conditions of total reproduction and improvement of virtual technologies has also become one of the most significant. The need to switch to full distance learning in connection with the pandemic had both its negative sides and contributed to the development of new educational ideas, gave rise to interesting and unexpected projects that cover a wide audience. In the modern world, there is a process of threatening discommunication associated with the gap between representatives of mass and elite culture, between different layers of the society. The difference is not so much between cultures, but rather there is a lack of understanding between social stratums of society, between age and social groups. In particular, the gap between the previous links in the author-critic-artist chain has increased. The situation in the modern world and art, associated with the collapse of traditionalism and the emergence of non-traditional structures, the time of re-evaluation, the search for new ways to translate cultural experience poses a problem for researchers and teachers to understand and adequately explain the latest processes and phenomena occurring in the artistic space, which should be reflected in art education. The theoretical concept of criticism and its special functions is being developed in the Russian visual art of the 21st century. It performs a special type of artistic, analytical, and creative activity. In different periods of the existence of art criticism, certain features of it came to the fore, depending on the paradigm of the era. Often in modern artistic activity, the functions of critic and curator are combined, the functions of these spheres of activity merge together. It is the critic and the curator who become the interpreters of a work of art and sometimes the perception of an artistic phenomenon or event depends on their interpretation. In the modern world, critics and curators often act as the creators of an artistic concept or a specific art event, and as analysts who evaluate the phenomena. Сriticism and curatorship are creative professions that perform not only the tasks of expertise and evaluation, they are the field of artistic creativity, they have their own creative role. The basis of such professional qualities can be an academic art school, which has all the necessary conditions to achieve the modern level of art studies. Moreover, modern criticism, penetrating the field of art, becomes a part of art itself. Therefore, in the modern cultural space, critics and curators can be more in demand, and sometimes more vividly realized, than even artists trained within the traditional academic system.